Chitotriosidase Activity and Gene Polymorphism in Iranian Patients with Gaucher Disease and Sibling Carriers - MOZAFARI, Hadi; TAGHIKHANI, Mohammad; KHATAMI, Shohreh; ALAEI, Mohammad Reza; VAISI-RAYGANI, Asad; RAHIMI, Zohreh (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Mozafari H, Taghikhani M, Khatami Sh, Alaei MR, Vaisi-Raygani A, Rahimi Z. Chitotriosidase Activity and Gene Polymorphism in Iranian Patients with Gaucher Disease and Sibling Carriers. Iran J Child Neurol. Autumn 2016; 10(4):62-70. Abstract Objective Chitotriosidase (CT) activity is a useful biomarker for diagnosis and monitoring of Gaucher disease (GD). Its application is limited by some variants in the CT gene. Two main polymorphisms are 24 bp duplication and G102S led to reduce CT activity. The aim of this study was to determine these variants influencing on plasma CT activity. Materials & Methods Blood samples were collected from 33 patients with GD, 15 sibling carriers and 105 healthy individuals serving as controls. CT activity was measured using 4-methylumbelliferyl-β-D-N,N′,N″triacetylchitotrioside substrate in plasma samples. The CT genotypes of 24 bp duplication and G102S variants were determined using PCR and PCR-RFLP. Results Untreated GD patients had a significantly higher CT activity compared to treated patients (P = 0.021). In addition, chitotriosidase activity in carriers was higher rather than controls. Allele frequencies of 24 bp duplication in GD patients, sibling carriers and controls were 0.21, 0.266 and 0.29 and for G102S were 0.318, 0.366 and 0.219, respectively. Different G102S genotypes had not significant effect on CT activity. Chitotriosidase activity has a positive correlation with age in normal group, carriers, and negative correlation with hemoglobin in GD patients. Using cut-off level of 80.75 nmol/ml/h, sensitivity and specificity of CT activity were 93.9% and 100%, respectively. Conclusion Chitotriosidase activity is a suitable biomarker for diagnosis and monitoring of GD. Determination of 24 bp duplication is helpful for more accurate monitoring the GD patient’s therapy. However, it seems that, specifying of the G102S polymorphism is not required for Iranian GD patients. References 1. Bennett LL, Mohan D. Gaucher disease and its treatment options. Ann Pharmacother 2013;47(9):1182-93. 2. Shrestha B, Devgan A, Sharma M. Gaucher’s disease: rare presentation of a rare disease. J Child Neurol 2013;28(10):1296-8. 3. Kanneganti M, Kamba A, Mizoguchi E. Role of chitotriosidase (chitinase 1) under normal and disease conditions. J Epithel Biol Pharmacol 2012;5:1-9. 4. Adly AA, Ismail EA, Ibraheem TM. Macrophagederived soluble CD163 level in young patients with Gaucher disease: relation to phenotypes, disease severity and complications. Int Immunopharmacol 2015;24(2):416-22. 5. Irún P, Alfonso P, Aznarez S, Giraldo P, Pocovi M. Chitotriosidase variants in patients with Gaucher disease. Implications for diagnosis and therapeutic monitoring. Clin Biochem 2013;46(18):1804-7. 6. Grace ME, Balwani M, Nazarenko I, Prakash- Cheng A, Desnick RJ. Type 1 Gaucher disease: null and hypomorphic novel chitotriosidase mutationsimplications for diagnosis and therapeutic monitoring. Hum Mutat 2007;28(9):866-73. 7. Woo KH, Lee BH, Heo SH, Kim JM, Kim GH, Kim YM, et al. Allele frequency of a 24 bp duplication in exon 10 of the CHIT1 gene in the general Korean population and in Korean patients with Gaucher disease. J Hum Genet 2014;59(5):276-9. 8. Wajner A, Michelin K, Burin MG, Pires RF, Pereira ML, Giugliani R, et al. Comparison between the biochemical properties of plasma chitotriosidase from normal individuals and from patients with Gaucher disease, GM1-gangliosidosis, Krabbe disease and heterozygotes for Gaucher disease. Clin Biochem 2007;40(5-6):365-9. 9. Rosén C, Andersson CH, Andreasson U, Molinuevo JL, Bjerke M, Rami L, et al. Increased Levels of Chitotriosidase and YKL-40 in Cerebrospinal Fluid from Patients with Alzheimer’s Disease. Dement Geriatr Cogn Dis Extra 2014;31;4(2):297-304. 10. Malaguarnera L. Chitotriosidase: the yin and yang. Cell Mol Life Sci 2006;63(24):3018-29. 11. Pagliardini V, Pagliardini S, Corrado L, Lucenti A, Panigati L, Bersano E, et al. Chitotriosidase and lysosomal enzymes as potential biomarkers of disease progression in myotrophic lateral sclerosis: A survey clinic-based study. J Neurol Sci 2015;15;348(1-2):245-50. 12. Fusetti F, von Moeller H, Houston D, Rozeboom HJ, Dijkstra BW, Boot RG, et al. Structure of human chitotriosidase. Implications for specific inhibitor design and function of mammalian chitinase-like lectins. J Biol Chem 2002;277:25537–25544. 13. Sista RS, Wang T, Wu N, Graham C, Eckhardt A, Bali D, et al. Rapid assays for Gaucher and Hurler diseases in dried blood spots using digital microfluidics. Mol Genet Metab 2013;109(2): 218–220. 14. Hollak CE, van Weely S, van Oers MH, Aerts JM. Marked elevation of plasma chitotriosidase activity. A novel hallmark of Gaucher disease. J Clin Invest 1994;93(3):1288–1292. 15. Old JM, Higgs DR. Gene analysis. In: Weatherall DJ, editor. Methods in hematology. The thalassemias. Vol. 6. London: Churchill Livingstone; 1983. pp.74 – 101. 16. Sinha S, Singh J, Jindal SK, Birbian N, Singla N. Association of 24 bp duplication of human CHIT1 gene with asthma in a heterozygous population of north India: a case-control study. Lung 2014;192(5):685-91. 17. Manno N, Sherratt S, Boaretto F, Coico FM, Camus CE, Campos CJ, et al. High prevalence of chitotriosidase deficiency in Peruvian Amerindians exposed to chitinbearing food and enteroparasites. Carbohydr Polym 2014;26;113:607-14. 18. Adelino TE, Martins GG, Gomes AA, Torres AA, Silva DA, Xavier VD, et al. Biochemical and Molecular Chitotriosidase Profiles in Patients with Gaucher Disease Type 1 in Minas Gerais, Brazil: New Mutation in CHIT1 Gene. JIMD Rep 2013;9:85-91. 19. van Dussen L, Hendriks EJ, Groener JE, Boot RG, Hollak CE, Aerts JM. Value of plasma chitotriosidase to assess non-neuronopathic Gaucher disease severity and progression in the era of enzyme replacement therapy. J Inherit Metab Dis 2014;37(6):991-1001. 20. Weinreb NJ, Aggio MC, Andersson HC, Andria G, Charrow J, Clarke JT, et al. Gaucher disease type 1: revised recommendations on evaluations and monitoring for adult patients. Semin Hematol 2004;41:15–22. 21. Czartoryska B, Tylki-Szymańska A, Górska D. Serum chitotriosidase activity in Gaucher patients on enzyme replacement therapy (ERT). Clin Biochem 1998;3(5):417-20. 22. Arndt S1, Hobbs A, Sinclaire I, Lane AB. Chitotriosidase deficiency: a mutation update in an african population. JIMD Rep 2013;10:11-6. 23. Lee P, Waalen J, Crain K, Smargon A, Beutler E. Human chitotriosidase polymorphisms G354R and A442V associated with reduced enzyme activity. Blood Cells Mol Dis 2007;39(3):353-60. 24. Chien YH, Chen JH, Hwu WL. Plasma chitotriosidase activity and malaria. Clin Chim Acta 2005 ;353(1-2):215 25. Bussink AP, Verhoek M, Vreede J, Ghauharalivan der Vlugt K, Donker-Koopman WE, Sprenger RR, et al. Common G102S polymorphism in chitotriosidase differentially affects activity towards 4-methylumbelliferyl substrates. FEBS J 2009;276(19):5678-88. 26. Aerts JM, Kallemeijn WW, Wegdam W, Joao Ferraz M, van Breemen MJ, Dekker N, et al. Biomarkers in the diagnosis of lysosomal storage disorders: proteins, lipids, and inhibodies. J Inherit Metab Dis 2011;34(3):605-19. 27. Giraldo P, Cenarro A, Alfonso P, Pérez-Calvo JI, Rubio- Félix D, Giralt M, et al. Chitotriosidase genotype and plasma activity in patients type 1 Gaucher’s disease and their relatives (carriers and non carriers). Haematologica 2001;86(9):977-84. 28. Pocovi M, Cenarro A, Civeira F, Torralba MA, Perez- Calvo JI, Mozas P, et al. Beta-glucocerebrosidase gene locus as a link for Gaucher’s disease and familial hypoalpha- lipoproteinaemia. Lancet 1998;351(9120):1919-23. 29. Fluiter K, van der Westhuijzen DR, van Berkel TJ. In vitro regulation of scavenger receptor BI and the selective uptake of high density lipoprotein choles-teryl esters in rat liver parenchymal and Kupffer cells. J Biol Chem 1998; 273:8434-8. 30. Ries M, Schaefer E, Lührs T, Mani L, Kuhn J, Vanier MT, et al. Critical assessment of chitotriosidase analysis in the rational laboratory diagnosis of children with Gaucher disease and Niemann-Pick disease type A/B and C. J Inherit Metab Dis 2006;29:647–652. 31. Kurt I, Abasli D, Cihan M, Serdar MA, Olgun A, Saruhan E, et al. Chitotriosidase Levels in Healthy Elderly Subjects. Ann N Y Acad Sci 2007;1100:185-8. 32. Tamanaha P, D’Almeida V, Calegare BF, Tomita LY, Bittencourt LR, Tufik S. 24 bp duplication of CHIT1 gene and determinants of human chitotriosidase activity among participants of EPISONO, a population-based cross-sectional study, São Paulo, Brazil. Clin Biochem 2013;46(12):1084-8. 33. Dodelson de Kremer R, Paschini de Capra A, Angaroni CJ, Giner de Ayala A. Plasma chitotriosidase activity in Argentinian patients with Gaucher disease, various lysosomal diseases and other inherited metabolic disorders. Medicina (B Aires). 1997;57(6):677-84. 34. Goldim MP, Garcia Cda S, de Castilhos CD, Daitx VV, Mezzalira J, Breier AC, et al. Screening of high-risk Gaucher disease patients in Brazil using miniaturized dried blood spots and leukocyte techniques. Gene 2012;508(2):197-8.